Denosumab is the first gene engineered agent for the treatment of osteoporosis - O A Nikitinskaya; Nataliya Vladimirovna Toroptsova (Современная ревматология)
The incidence of osteoporosis (OP) is growing steadily. Practitioners who long follow up patients with OP frequently ask questions about the duration of treatment with this or that drug particularly in cases of severe OP and at high risk for new fractures when these agents have been used for years and about the possibility and necessity of switching of the patient from one to other therapy. Individual drug tolerance and longterm treatment adherence are of fundamental importance in organizing care to patients with OP are of fundamental importance. Low (<80%) compliance gives rise to the lower efficacy of antiosteoporotic drugs in preventing the risk of fractures, worsening the end result of treatment as compared to that obtained in the clinical trials proving the expediency of their intake. For the more qualitative prevention and treatment of OP, novel antiosteoporotic drugs are being designed and the frequency of their administration investigated. The paper gives data on denosumab, the first gene engineered drug for the treatment of postmenopausal OP, on the mechanism of its action, efficacy and safety during its long-term use, and on the possibility of switching to its usage after bisphosphonate treatment.